Health-related quality of life in gynecological oncology: Instruments and psychometric properties. Issue 1 (1st January 2003) - Boling, W.; Fouladi, R. T.; Basen-Engquist, K.
Abstract : Quality of life is generally recognized as a subjective, multidimensional concept, which places emphasis on the self-perception and subjective experience of the patient compared to the expectation of an individual's current health state. Health-related quality of life, which encompasses the psychological, physical, and social functioning of patients, has evolved over recent decades into an established treatment outcome in cancer clinical trials. Assessing quality of life as a clinical trial outcome enables clinicians to better address concerns of gynecological oncology patients, but selection of appropriate measurement tools is critical. This article reviews the concepts of reliability and validity, and describes three health-related quality of life instruments, their psychometric properties, and their use in gynecological oncology clinical trials and other cancer research.